Pemeliharaan Warisan Pendidikan Islam Melalui Tradisi Surau Dan Pesantren di Nusantara - Irmayanti, Azizah Putri; Zulmuqim, Zulmuqim; Kosim, Muhammad (Yayasan Rahmat Islamiyah, 2024)
This article aims to analyze the legacy of Islamic education at the beginning of its entry in the archipelago, analyze the surau tradition in inheriting Islamic education and analyze the pesantren tradition in inheriting Islamic education in the archipelago. The research method used in this study is the historical method. Surau and pesantren are traditional educational institutions that have long been rooted in the Muslim community in the archipelago. Both institutions have played an important role in maintaining the heritage of education in Indonesia. Surau and pesantren not only teach religious sciences, but also moral values and noble character. The teaching methods in surau and pesantren are holistic, emphasizing the balance of knowledge, morals, and spirituality. In addition, these two institutions are also the basis for the regeneration of Muslim scholars and intellectuals. Although there are now many modern Islamic educational institutions, surau and pesantren still exist because of their ability to adapt to the times without abandoning their traditional values. The maintenance of surau and pesantren is important to maintain the intellectual heritage and wealth of Islamic treasures in the midst of modernization. Optimizing the role of surau and pesantren in Islamic education is needed, among others, by revitalizing the curriculum, improving the quality of teachers, and economic empowerment. Thus, the heritage of Islamic education is maintained while being relevant to the needs of contemporary society. This article provides a comprehensive overview of how the surau and pesantren traditions are not only the protectors of Islamic values, but also the glue of local culture and the support of adaptive Islamic education in the face of changing times.Â